2022
DOI: 10.1155/2022/2091677
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation after Primary Resection of Atypical Lipomatous Tumors of the Extremity Reduces Local Recurrence but Increases Complications: A Multicenter Evaluation

Abstract: Background. Radiation after resection of an atypical lipomatous tumor (ALT) is controversial. This study evaluates local control and complications after the first resection of ALTs of the extremity with or without adjuvant radiation. Methods. A dual institution, retrospective review of patients treated from 1995 to 2020 with first-time resection of an ALT in the extremity was performed. In total, 102 patients underwent adjuvant radiation (XRT group) and 68 patients were treated with surgery alone (no-XRT group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Radiation therapy (RT) can be used as an adjuvant treatment strategy to improve local tumor control. Although the role of RT in management of deep-seated ALT of the extremities is controversial, several studies have shown that RT in combination with surgery is associated with a lower risk of local recurrence (36)(37)(38)(39). Radiation doses typically range from 50 to 70 Gy (39).…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation therapy (RT) can be used as an adjuvant treatment strategy to improve local tumor control. Although the role of RT in management of deep-seated ALT of the extremities is controversial, several studies have shown that RT in combination with surgery is associated with a lower risk of local recurrence (36)(37)(38)(39). Radiation doses typically range from 50 to 70 Gy (39).…”
Section: Managementmentioning
confidence: 99%
“…Although the role of RT in management of deep-seated ALT of the extremities is controversial, several studies have shown that RT in combination with surgery is associated with a lower risk of local recurrence (36)(37)(38)(39). Radiation doses typically range from 50 to 70 Gy (39). Long-term risk of radiationinduced sarcomas has not been reliably assessed in these studies.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadly, it is not uncommon for these tumours to recur after primary resection, and so this team from Nashville (Tennessee, USA) have sought to establish whether or not radiation has a role to play in the management of these unusual tumours. 3 Using data from two institutions, the team chose to assess the achievement of local control as their outcome of interest and sought to establish how this varied with the provision of adjuvant radiotherapy. They also reported on the complications seen after primary resection of ALT.…”
Section: Adjuvant Radiation In Atypical Lipomatous Tumoursmentioning
confidence: 99%